Instrumentos didáticos no trabalho docente: o texto narrativo como objeto de ensino - ABREU, Inéia Damasceno (2007)
This work intends to discuss about the used didactic instruments in teaching practices of narrative texts. This quarrel consists of the description and analysis of the ways that the teacher uses these instruments to provide to the pupils the meeting with the education object, taking them to appropriate of the capacity of production of narrative texts, transforming, thus, the teaching object in object effectively taught. In this context, the corpus of this research elapses of interviews, questionnaires, recording in audio and video and notations in daily of field about lessons of Portuguese language that we observed in the second semester of the school year in 2006. The collect of data happened in a class of 4th stage of the Education of Young and Adults of a public school of the periphery of the Castanhal city, in Pará. On the theoretical point of view, we search the contributions of Geraldi (2002) and Bakhtin (1929/1986) about the interacionista conception of language and the contributions produced in the area of the didactics of the languages by the group of studies of Geneva coordinated for Schneuwly, Dolz and collaborators (2000, 2001, 2004, 2005), in reference to the teacher’s work and the elements that composes it (didactic gestures and instruments). On the methodologic point of view, we appropriated of the contributions of André (2000, 2005) and Bogdan & Biklen (1999), to direct the procedures of constitution of the data following the studies of the ethnographic research. The analysis of the data allowed us to affirm that the ways as the professor uses some didactic instruments direct his teaching practice of Portuguese Language in order to promote the appropriation of knowledge about narrative text by the pupils. This practices show the heterogeneous character of his work when they present characteristics of the teaching considered traditional, that considers the representacionista conception of language, and characteristics of the teaching of language based on the textual linguistics that considers the language as interaction form.